Stakeholders and sustainability disclosure: Evidence from an emerging market - Inusah Sulemana; Limei Cheng; Andrew Osei Agyemang; Abednego Osei; Timothy Masuni Nagriwum (Sustainable Futures)
This study examines the relationship between stakeholders’ pressure and sustainability disclosure. This study used primary data from 214 participants from Ghana's mining and manufacturing firms. SmartPLS version 4 software was used to run the study's analysis following the Partial Least Square Structural Equation Modeling (PLS-SEM) approach. This study's results revealed that pressures from stakeholders (government, shareholders, and customers) significantly influence green technological innovation and sustainability disclosure. Additionally, green technological innovation mediates the relationships between government, shareholder, and customer pressure and sustainability disclosure. Additionally, corporate culture partially moderates the relationships between stakeholders’ (shareholder and customer) pressure and sustainability disclosure.